Polish Population Censuses in the 19th and 20th Centuries: Scope and Subject Matter in the Context of International Standards - Leszczyńska, Cecylia (Studia Historiae Oeconomicae, 2022)
his paper analyses the population censuses on the Polish area, particularly, the subject of censuses and their thematic scope. the study refers to the censuses in the 19th and 20th centuries (the study closes with the 1988 census). The paper consists of three parts. The first one presents the origins of censuses and the first censuses conducted in Europe in the 18th century. This part also shows the efforts of international statistical institutions to normalise and standardise national censuses. It allowed for building international standards to make national censuses comparable. The second part shows censuses in the 19th century, and the third part discusses censuses in the 20th century. A fundamental feature of the censuses is a set of questions common to demographic and social issues. This makes it possible to carry out comparative analysis in different regional cross-sections on a secular basis. It should also be provided that census categories are not always comparable, hence various conversions and estimates are necessary. The universality of the censuses have made them a huge organizational challenge each time. The greatest effort was borne by the statistical institutions responsible, not only for conducting the censuses, but also during the compilation and publication of the data.